If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -17 = 19x + -6 Reorder the terms: -17 + -3x = 19x + -6 Reorder the terms: -17 + -3x = -6 + 19x Solving -17 + -3x = -6 + 19x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-19x' to each side of the equation. -17 + -3x + -19x = -6 + 19x + -19x Combine like terms: -3x + -19x = -22x -17 + -22x = -6 + 19x + -19x Combine like terms: 19x + -19x = 0 -17 + -22x = -6 + 0 -17 + -22x = -6 Add '17' to each side of the equation. -17 + 17 + -22x = -6 + 17 Combine like terms: -17 + 17 = 0 0 + -22x = -6 + 17 -22x = -6 + 17 Combine like terms: -6 + 17 = 11 -22x = 11 Divide each side by '-22'. x = -0.5 Simplifying x = -0.5
| logx=0.3010 | | x-1/2-x-2/3=1/2 | | 4-6/18-14 | | y2-y1/x2-x1= | | (5-x)(1+x)=0 | | m^2+2m+4= | | -2yx^2+y^2=25 | | 3x-1/4=4x-1/3 | | (4sin^2(x))-4cosx+1=0 | | 8(7m+8)=y | | 2(3x-7)-(6-x)=4-(x-5) | | 25(2x-1)=6(x+3)+3x | | v=4/3Π×9^ | | Z/1.6=1.1 | | 4x^3+2x^2+0.25x=0.173 | | x^2-y^2=201 | | 2=(x-1.97)/1.97 | | 2x-1/x^2=0 | | ln(4x^2)+ln(8)=5 | | 4/3•3.14•8 | | 8+7=12x-3-8x+1 | | 3x/7=10-x/2 | | y+7x=32 | | x^(3/4)=4 | | 2b+3(3b+19)=25 | | 2y-3x=-48 | | 3x+2y=-48 | | (4C-1)(5C+3)=0 | | xNy=2xy^2 | | 11x(751+209)= | | -2+5x=3x | | (-3b-1/4)-8 |